Riding the Waves of Technology: A Proposed Model for the Selection of Appropriate Computerized Accounting Software for Implementation in SMEs in Developing Countries - Aduamoah, Maurice; Yinghua, Song; Anomah, Sampson; Ahmed, Fawad (Archives of Business Research, 2017)
Currently, SMEs are looking for ways to select Computerised Accounting Software packages to better improve their business process capabilities, economies of scale and competitive edge over rivalry companies in the market. CAS is seen as the optimal preference as it is now a dominant, powerful and integrated software package embedded with all the modules needed to process and generate accounting information on a timely, high precision and error free manner for management decisions. However, choosing the appropriate CAS has become a critical problem for many SME entities in developing countries as the past and continuous selection of sub-optimal CAS application had brought mischance’s to SMEs leading to massive financial losses and arguably bankruptcies. Some critical and vital considerations such as vendor credentials, CAS selection and implementation financing option by the CAS vendor,Maintenance overheads, Functionality, Flexibility and Implementation are most often marginalised during the selection process which have negatively affected SMEs ability to select the best breeds of CAS among the proliferated software in the software market in Ghana. This study fills this gap by proposing an appropriate integrated buying framework leading to a mathematical model that may guide SMEs in their quest to selecting an optimal CAS package for implementation where the software market is fuzzy and unclear regarding the best CAS package available. Business processing needs of SMEs are varied so it is expected that the suggested model would support SMEs in developing countries select the “most appropriate” CAS that may meet their respective financial transaction processing needs.